Holding the passive accountable: a didactic sequence proposal that integrates ELT and CSE - Torres, Andrea (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
The following didactic sequence aims at raising awareness of gender-based violence in the context of the International Day for the Elimination of Violence against Women (November 25th). This issue provides the setting for activities to develop students’ reading comprehension skills, and to analyse the uses of the passive voice. Consequently, we can reflect on the significance of the linguistic forms we choose, and the effect they have on the way we construct social realities. Deconstructing texts give teachers and students the opportunity to challenge discourse practices and to engage in critical thinking. Keywords: ELT - didactic sequence - CSE - reading comprehension - passive voice.